PERAN CITRA MEREK MEMEDIASI PENGARUH IKLAN TERHADAP KEPUTUSAN PEMBELIAN ES KRIM WALL’S MAGNUM - Putri, Ni Putu Jessica Maharani; Kusumadewi, Ni Made Wulandari (E-Jurnal Manajemen; Vol 7 No 8 (2018)DO - 10.24843/EJMUNUD.2018.v07.i08.p12, 2018)
ABSTRACT The current development of the advertising world continues to increase, making the company selectiv in creating creative and engaging advertisements to provide a brand image that can attract consumers in purchasing decisions. The purpose of this study was to determine the role of brand image mediating the influence of advertising on purchasing decisions of Wall's Magnum ice cream. This research was conducted in Kecamatan Kuta. The number of samples taken as many as 100 samples with nonprobability sampling method. The data was collected through questionnaires with likert scale 1-5. The analysis technique used is path analysis (Path analysis). Based on the results of the analysis found that ads have a positive effect on brand image, brand image positively affects purchasing decisions, advertising positively affects purchasing decisions and brand image mediates the effect of advertising on purchasing decisions. Advice for companies, if you want to improve purchasing decisions should pay attention to advertising and brand image. Suggestions for future researchers are to research using variables other than the influence of advertising, brand image to examine purchasing decisions.   Keywords : Brand Image, Advertisement, Purchase Decision